Problematização no Programa Integrado de Saúde Coletiva - medicina UniEVANGÉLICA - Cristiane Martins R. Bernardes; Juliana Késia Martins de Sousa; Ricardo de Oliveira Resende (UniEVANGÉLICA, 2012)
This paper proposes a reflection on the use of the Problematization methodology in the instruction of Public Health of UniEVANGELICA's Medical School. The objective of this study is to show characteristics of the methodology through the existing literature and to report its empirical application in the course. To accomplish that, the paper discusses initially the teaching methods and their different approaches, focusing on Problematization, moving on to the experience report, aiming to point out the facility and the limitations perceived in its use on Medicine teaching.